2008
DOI: 10.1016/j.fuel.2007.05.011
|View full text |Cite
|
Sign up to set email alerts
|

NO reduction capacity of four major solid fuels in reburning conditions – Experiments and modeling

Abstract: The combustion of solid fuels in the rotary kiln and in the calciner of a cement plant generates fuel and thermal NO. This NO can be reduced inside the reducing zone of the calciner. This occurs in two different ways: homogeneous reduction by hydrocarbons and heterogeneous reduction by char. The purpose of this paper is to identify the relative contribution of volatile matters or char on the NO reduction process, which largely depends on the nature of the solid fuel used for reburning. Experiments were underta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Much research has been performed, showing detailed kinetic mechanisms being compared to experimental results, concerning the profile of species as a function of time. Examples are the work of Baldwin et al [22], Morley [23], Slagle et al [24], Hughes et al [25], Baulch et al [26] and others [27][28][29][30][31]. Often, these mechanisms describe the oxidation or auto-ignition of one fuel and often the mechanisms are detailed.…”
Section: Introductionmentioning
confidence: 99%
“…Much research has been performed, showing detailed kinetic mechanisms being compared to experimental results, concerning the profile of species as a function of time. Examples are the work of Baldwin et al [22], Morley [23], Slagle et al [24], Hughes et al [25], Baulch et al [26] and others [27][28][29][30][31]. Often, these mechanisms describe the oxidation or auto-ignition of one fuel and often the mechanisms are detailed.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction of nitrogen monoxide with char is of special interest due to its importance in producing or reducing NO emission from combustion system such as fluidized bed or pulverized coal combustion boiler [1][2][3][4][5][6][7]. Most published studies focused on common temperatures in fluidized bed, which are between 873 and 1,273 K [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In the combustion process, mechanisms of the formation and reduction of NOx are extremely crucial and have been studied extensively [15][16][17][18][19]. Julien Cances [20] conducted experiments and modelling with four major solid fuels to identify the difference in the contributions of volatile matters and char to the NOx reduction, and found that for a short initial residence time, volatiles contribute more to the NOx reduction than char, and that after the short initial residence time, char contributes more. The influence of different factors (hydrocarbons, homogenous reactions, heterogeneous reactions, particle size, dried sludge, ash, etc.)…”
Section: Introductionmentioning
confidence: 99%